2014
DOI: 10.4028/www.scientific.net/kem.604.313
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sapropel in Development of Effective Thermal Insulating Materials

Abstract: This paper presents investigations of thermal conductivity, tensile strength and compressive stress at 10% deformation of effective thermal insulation composites made from hemp shives and sapropel. Images of hemp shives and hemp composite microstructure obtained by scaning electron microscope (SEM) are analised. The paper presents properties of composite from seven compositions. Composite forming mixture contains different amount of sapropel as well as paper production wastes (PPW) obtained in paper processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Graphical correlation between compressive strength and density can be seem in Fig.3. If the results are compared to similar studies, then it can be seen that achieved thermal conductivity is adequate for sapropel thermal insulation materials as it is around 0,053 W/m*K [30], [31]. But if compared to other hemp materials, for example, a hemp lime concrete, then it has superior thermal conductivity as hemp-lime materials have it around 0,075 W/m*K [32], although their mass is also larger.…”
Section: Resultsmentioning
confidence: 89%
“…Graphical correlation between compressive strength and density can be seem in Fig.3. If the results are compared to similar studies, then it can be seen that achieved thermal conductivity is adequate for sapropel thermal insulation materials as it is around 0,053 W/m*K [30], [31]. But if compared to other hemp materials, for example, a hemp lime concrete, then it has superior thermal conductivity as hemp-lime materials have it around 0,075 W/m*K [32], although their mass is also larger.…”
Section: Resultsmentioning
confidence: 89%
“…Also, it was demonstrated that composite materials that were made using hemp shives and SP had exceptional thermal and acoustic properties [18][19][20]. The compressive strength of such composites was 0.61-0.28 MPa, whereas their density was 210-410 kg/m 3 .…”
Section: Introductionmentioning
confidence: 99%